Proceedings of the Thirty-Ninth Annual ACM Symposium on Theory of Computing 2007
DOI: 10.1145/1250790.1250860
|View full text |Cite
|
Sign up to set email alerts
|

Lattices that admit logarithmic worst-case to average-case connection factors

Abstract: We demonstrate an average-case problem which is as hard as finding γ(n)-approximate shortest vectors in certain n-dimensional lattices in the worst case, where γ(n) = O( √ log n).The previously best known factor for any class of lattices was γ(n) =Õ(n).To obtain our results, we focus on families of lattices having special algebraic structure. Specifically, we consider lattices that correspond to ideals in the ring of integers of an algebraic number field. The worst-case assumption we rely on is that in some p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…Namely, we can obtain bootstrappable schemes in any given dimension, but of course the schemes in low dimensions will not be secure. Our (rather crude) analysis suggests that the scheme may be practically secure at dimension n = 2 13 or n = 2 15 , and we put this analysis to the test by publishing a few challenges in dimensions from 512 up to 2 15 .…”
Section: Our Implementationmentioning
confidence: 99%
“…Namely, we can obtain bootstrappable schemes in any given dimension, but of course the schemes in low dimensions will not be secure. Our (rather crude) analysis suggests that the scheme may be practically secure at dimension n = 2 13 or n = 2 15 , and we put this analysis to the test by publishing a few challenges in dimensions from 512 up to 2 15 .…”
Section: Our Implementationmentioning
confidence: 99%
“…Peikert and Rosen [PR07] provided a reduction of an average-case lattice problem to the worstcase hardness of ideal lattice problem, where the lossiness of the reduction was only logarithmic over fields of small root discriminant. Gentry [Gen10] showed that ideal lattice problems are efficiently self-reducible (in some sense) in the quantum setting.…”
Section: Computational Hardness Assumptions Over Number Fieldsmentioning
confidence: 99%
“…Note that all prior works on R-SIS except [32] used the polynomial embedding. However, the canonical embedding representation is mathematically sounder, and the unification leads to a more natural connection between R-SIS and R-LWE.…”
Section: Polynomial Representation Versus Canonical Embeddingmentioning
confidence: 99%
“…This problem is suspected to be extremely hard in the worst case for values of γ that are polynomial in the lattice dimension. But it is easy for ideal lattices, as Minkowski's bound on the lattice minimum is known to be essentially sharp in that case (see, e.g., [32,Se. 6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation